Peran Penting Pendidikan Karakter dalam Science Learning Berbasis Ke Islaman - Noorrahma Ika Adiati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Science learning have a important role in the formation of human character, one of which is through scientific thinking skills and habits that can be used as material on build morals, character and morals to underlie national education on character building. Science learning serves as a benchmark approach to build a person’s character in building a personality in himself. This study aims to understand the concept of character education from a hadits perspective through a contextual and non-contextual understanding study. Data were collected from various referensces which were analyzed with an approach through the understanding of a core analysis. The research showed the results that the hadits studied in this study contained the patterns or behavior of human life. Character education will be seen more clearly with the hadits of the Prophet, especially those containing character education so that the quantuty of hadits and character requires Muslim scholars to take advantage of character education sourced from the Qur’an and hadits. The Qur’an and hadits of the Prophet can be applied through several aspects of their foundation and scope. Related to cases of rampant crime that befell the world of education in Indonesia. We as students must able to neutralize this problem through a syar’I review which refers to the hadits of the Prophet Muhammad in the Qur’an.